PENGARUH PROFITABILITAS, STRUKTUR MODAL, UKURAN PERUSAHAAN, DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN - Fabian, Christopher; Wijaya, Henryanto (Jurnal Paradigma Akuntansi, 2024)
This study aims to analyze the effect of profitability, capital structure, firm size, and good corporate governance on firm value in 40 manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020 as a research sample where panel data regression analysis was carried out. The data processing in this study uses the EVIEWS 12 application. The results of this study indicate that profitability and firm size have a significant positive effect on firm value, while capital structure, board of commissioners and audit committees have no significant negative effect on firm value. The implication of this research is the need to pay attention to the ratios that affect firm value, so as to increase firm value.